Report of intraosseous intravascular papillary endothelial hyperplasia associated with an odontogenic cyst in the maxilla and literature review - Mateus José Dutra; Ana Lia Anbinder; Christyan Moretti Pereira; Beatriz Afonso Chiliti; André Caroli Rocha; Estela Kaminagakura (BMC, 2024)
Abstract Intravascular papillary endothelial hyperplasia (IPEH) represents an uncommon reactive endothelial hyperplastic proliferation. A 46-year-old man experienced increased volume in the right maxilla, elevation of the nasal ala, and swelling of the hard palate with a reddish hue for 3 months. Computed tomography revealed an expansive hypodense region and cortical bone destruction associated with an impacted supernumerary tooth and an endodontically treated tooth. Under the differential diagnoses of a radicular cyst, dentigerous cyst, and ameloblastoma, an exploratory aspiration and incisional biopsy were performed. This revealed the formation of blood vessels of various diameters lined by endothelium, forming intravascular papillae positive for CD-34. The definitive diagnosis was IPEH, and the patient was treated by embolization and surgery. Histological analysis confirmed the presence of IPEH associated with an odontogenic cyst. After 12 months of follow-up, no recurrence was observed. Also, we reviewed case reports of IPEH affecting the maxilla and mandible. Fourteen intraosseous cases were reported in the maxilla and mandible, with a preference for males and affecting a wide age range. Complete surgical excision was the treatment of choice, and recurrences were not reported. The pathogenesis of IPEH is controversial and may originate from trauma or inflammatory processes. To the best of our knowledge, this is the first report of an association of IPEH with an odontogenic cyst. The importance of IPEH in the differential diagnosis of intraosseous lesions in the jaws is emphasized, and preoperative semiotic maneuvers are needed to prevent surgical complications.